2020
DOI: 10.1109/jphot.2020.2966256
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Finite Element Method: Electromagnetic Propagation in Bent Waveguides

Abstract: A new hybrid finite element method (HFEM) was developed, using basis functions of first and second order, to analyse the electromagnetic wave propagation in three types of waveguides: disk waveguides, ring waveguides and cylindrical waveguides. For validation purposes, results obtained with the HFEM method were compared with those obtained with a recursive finite element method (RFEM) and with two different analytical methods. The domain discretization effect on the results of the new HFEM method was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The EOT is an optical phenomenon, in which a structure containing subwavelength apertures transmits more light than might naively be expected. Ebbesen et al observed that when focusing a light beam in a thick metallic film where there was a subwavelength hole array, a large increase of incident electromagnetic wave transmission occurs, i.e., a periodic array of subwavelength holes, as presented in Figure 5, transmits more light than a large macroscopic hole with the same area as the sum of all the small holes [1,2,[13][14][15][16][17][18][19]. This discovery would be fundamental, as it not only allowed great technological developments during the last decade, but also allowed a better understanding of the diffraction by small slits in relation to the light wavelength [20,21].…”
Section: Aperture Nanoantennasmentioning
confidence: 99%
See 2 more Smart Citations
“…The EOT is an optical phenomenon, in which a structure containing subwavelength apertures transmits more light than might naively be expected. Ebbesen et al observed that when focusing a light beam in a thick metallic film where there was a subwavelength hole array, a large increase of incident electromagnetic wave transmission occurs, i.e., a periodic array of subwavelength holes, as presented in Figure 5, transmits more light than a large macroscopic hole with the same area as the sum of all the small holes [1,2,[13][14][15][16][17][18][19]. This discovery would be fundamental, as it not only allowed great technological developments during the last decade, but also allowed a better understanding of the diffraction by small slits in relation to the light wavelength [20,21].…”
Section: Aperture Nanoantennasmentioning
confidence: 99%
“…This phenomenon is known as surface plasmon. At specific optical frequencies the nanoantenna resonates at the same frequency as the incoming light which enables the absorption of the incoming radiation [ 4 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
See 1 more Smart Citation